L’article 23 de la Charte africaine des droits de l’homme et des peuples : le silence juridique sur le concept du principe de solidarité - Damsou Kindé (Revue Interventions Économiques)
ABSTRACTThe cooperation between the African Union Member States stands out by Article 23 of the African Charter on Human and Peoples' Rights which establishes the Principle of Solidarity that binds in some ways these States in their relations. This Principle of Solidarity, which is taken up again in Article 3(a) of its Constitutive Act, manifests itself in the need for its Member States to achieve a high degree of Unity and Solidarity among themselves and their peoples in order to develop strategies for democracy and good governance, as well as mechanisms to guarantee fundamental freedoms. This contribution is a critical analysis of Article 23 of the Banjul Charter. It considers concrete examples that illustrate the manifestation of the Principle of Solidarity. The approach is pragmatic with a deductive study of the role of the African Union in promoting this Charter.